Infrastructure and Ops Hour with Sam Newman. (O'Reilly Media, Inc., 2022)
Our data management solutions no longer match the complexity of organizations, the proliferation of data sources, and the scope of our aspirations to get value from data with AI and analytics. These pain points have led to a new paradigm: the data mesh. Join us for a special conversation on data mesh with Sam Newman and data mesh founder Zhamak Dehghani. They'll discuss how we got to this inflection point with data, then dive into some of the benefits (and challenges) of data mesh--treating data as a product that considers domains as a primary concern and applies platform thinking to create self-serve data infrastructure. This is a chance for you to hear Sam and Zhamak speak about infrastructure and ops and their own career journeys. They'll spend a few minutes covering the trends that are influencing infrastructure, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Explore the origins and opportunities of the data mesh approach See what's coming next for infrastructure and ops This recording of a live event is for you because... You want to learn about data mesh, data as a product, and what that means for operations. You're looking for ways to implement data best practices and streamline your value delivery. Recommended follow-up: Read Data Mesh (early release book) Attend Data Mesh in Practice--with Interactivity (live online training course with Max Schultze and Arif Wider) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.